Pendidikan Tasawuf dalam Membentuk Sikap Nasionalis-Religius Santri di Pondok Pesantren Ngalah Pasuruan - Murtadlo, Ahmad Zuhal (CV. Satria Jaya, 2024)
This study is concerned with Sufism education which is seen as an alternative model of Islamic religious education in instilling comprehensive Islamic values ​​in students in the context of Indonesia with its high level of heterogeneity. The main focus of this study is based on Sufism education in forming nationalist-religious attitudes at the Ngalah Islamic Boarding School, namely: 1) the concept of Sufism education, 2) the process of Sufism education in forming nationalist-religious attitudes, and 3) forms of nationalist-religious attitudes at the Ngalah Islamic Boarding School. To get a natural picture of the research, qualitative research was conducted to understand the essence of a series of daily events in a particular community. This qualitative research was chosen to describe, understand, and interpret the phenomena, events, and social activities that occur in the Ngalah Pasuruan Islamic boarding school—data collection techniques through observation, interviews, and document analysis. From the field study, the following findings were obtained: First, the concept of Sufism education in the Ngalah Islamic boarding school uses the tarekat system, while the Naqsyabandiyyah Khalidiyyah tarekat as an institution of Sufism education, and the Naqsyabandiyyah Khalidiyyah tarekat is one of the Mu'tabarah Thariqah. Second, the Sufism education process is carried out comprehensively, reflecting the integration between cognitive, psychomotor, and affective, balanced between the practice of ritual worship and social. In the process, it was found that there was a habituation of spirituality in the Ngalah Islamic Boarding School which was an important component in the formation of a Nationalist-Religious attitude. Third, the form of Nationalist-Religious attitudes include attitudes of faith and piety, patience, tolerance, togetherness and unity, family and affection, balance, love of the homeland, love of culture and national customs. The results of this study have theoretical conclusions as the development of Islamic education curriculum, can be implemented in all educational environments, simple, effective, and efficient in achieving the goals of instilling faith and piety, fostering spiritual and physical, ritual and social piety and having a nationalist-religious attitude that embodies the concept of Pancasilaism and Bhineka Tunggal Ika, while the practical implications are to smooth the mental revolution movement echoed by the government through the spiritual revolution movement.